RNA Polymerases of Maize: Partial Purification and Properties of the Chloroplast Enzyme - Bottomley, Warwick (1971)
A DNA-dependent RNA polymerase has been solubilized and partially purified from washed chloroplasts prepared from maize seedlings. The purified enzyme was completely dependent on added DNA after purification by phospho- or DEAE-cellulose chromatography. On glycerol density gradients, the enzyme ran ahead of a marker with a sedimentation constant of 18 S, indicating a molecular weight of 500,000 or more. The instability of the highly purified enzyme made intensive study difficult, but the properties of the enzyme purified by phosphocellulose chromatography are reported. Template specificity varied during purification but the activity was always higher with denatured than with native DNA and the preference for maize DNA over calf-thymus DNA increased during purification. The enzyme required magnesium for optimal activity, was inhibited by salt concentrations in excess of 0.1 M, and had a temperature optimum of 48°C. The chloroplast enzyme differed from similar activities so far reported from maize or other sources, particularly in the high salt concentrations needed to elute it from phosphocellulose. The soluble, DNA-dependent enzyme was not inhibited by either α-amanitin or by rifamycin-SV under the assay conditions used.